Antisense‐mediated therapeutic pseudoexon skipping in TMEM165‐CDG. (22nd May 2014) - Yuste‐Checa, P.; Medrano, C.; Gámez, A.; Desviat, L.R.; Matthijs, G.; Ugarte, M.; Pérez‐Cerdá, C.; Pérez, B.
<x xml:space="preserve">Abstract</x> Deficiencies in glycosyltransferases, glycosidases or nucleotide‐sugar transporters involved in protein glycosylation lead to congenital disorders of glycosylation (CDG), a group of genetic diseases mostly showing multisystem phenotype. Despite recent advances in the biochemical and molecular knowledge of these diseases, no effective therapy exists for most. Efforts are now being directed toward therapies based on identifying new targets, which would allow to treat specific patients in a personalized way. This work presents proof‐of concept for the antisense RNA rescue of the Golgi‐resident protein TMEM165, a gene involved in a new type of CDG with a characteristic skeletal phenotype. Using a functional in vitro splicing assay based on minigenes, it was found that the deep intronic change c.792+182G>A is responsible for the insertion of an aberrant exon, corresponding to an intronic sequence. Antisense morpholino oligonucleotide therapy targeted toward TMEM165 mRNA recovered normal protein levels in the Golgi apparatus of patient‐derived fibroblasts. This work expands the application of antisense oligonucleotide‐mediated pseudoexon skipping to the treatment of a Golgi‐resident protein, and opens up a promising treatment option for this specific TMEM165‐CDG.